Analysis of in vivo absorption of didanosine tablets in male adult dogs by HPLC - Severino, Patrícia; Silva, Heloisa [UNESP]; Souto, Eliana B.; Santana, Maria Helena A.; Dalla Costa, Teresa Cristina T. (Elsevier, 2012)
Didanosine is an effective antiviral drug in untreated and antiretroviral therapy-experienced patients with Human Immunodeficiency Virus (HIV). An automated system using on-line solid extraction and High Performance Liquid Chromatography (HPLC) with ultraviolet (UV) detection was developed and validated for pharmacokinetic analysis of didanosine in dog plasma. Modifications were introduced on a previous methodology for simultaneous analysis of antiretroviral drugs in human plasma. Extraction was carried out on C18 cartridges, with high extraction yield as stationary phase, whereas mobile phase consisted of a mixture of 0.02 M potassium phosphate buffer, acetonitrile (KH2PO4: acetonitrile: 96:4, v/v) and 0.5% (w/v) of heptane sulphonic acid. The pH was adjusted to 6.5 with triethylamine. All samples and standard solutions were chromatographed at 28 °C. For an isocratic run, the flux was 1.0 mL/min, detection was at 250 nm and injected volume was 20 μL. The method was selective and linear for concentrations between 50 and 5000 ng/mL. Drug stability data ranged from 96% to 98%, and limit of quantification was 25 ng/mL. Extraction yield was up to 95%. Drug stability in dog plasma was kept frozen at -20 °C for one month after three freezethaw cycles, and for 24 h after processing in the auto sampler. Assay was successfully applied to measure didanosine concentrations in plasma dogs. © 2012 Xian Jiaotong University. Productionand hosting by Elsevier B.V. All rights reserved.
Keywords: Didanosine; HPLC; Male dogs; On-line solid phase extraction